Correction: Balkrishna et al. Application of Zebrafish Model in the Suppression of Drug-Induced Cardiac Hypertrophy by Traditional Indian Medicine Yogendra Ras. Biomolecules 2020, 10, 600 - Acharya Balkrishna; Yashika Rustagi; Kunal Bhattacharya; Anurag Varshney (Biomolecules)
Error in Figure [...]